Stats for Africa: Bless, C & Kathuria, R (1993) Fundamentals of social statistics: An African Perspective. Cape Town: Juta. 367 pages. - Collings, Steven J (PINS-Psychology in Society, 2026)
There is little doubt that students and new research worker will find this book of great value. Bless and Kathuria have produced a very practical and down-to-earth introduction to social statistics which is likely to go a long way towards dispelling the negative attitudes and beliefs that many social science students bring to statistics courses. Descriptive, propositional, and inferential statistics are presented in a systematic and "user-friendly" manner. The book is laced throughout with instructive illustrations and examples--which have been selected to reflect a particularly African perspective--and students are provided with numerous exercises that they can work through to test their understanding of the concepts dealt with.